A strength estimation method for aluminum alloy butt welded joints with mismatched mechanical properties. (October 2022) - Wang, Jianing; Chen, Xin; Yang, Lifei; Zhang, Guanchen
Abstract: Aluminum alloy thin-walled welded structures have been widely used in automotive lightweight design. However, during the welding process of aluminum alloy sheets, the mismatched welded joints with different microstructure and mechanical properties are formed. The entire mismatched welded joint can be divided into four zones, including welded zone (WZ), hardening heat affected zone (HZ), softening heat affected zone (SZ) and base metal zone (BM). This study aims to analyze the effects of mechanical properties and geometrical characteristics of different welding zones on the load-bearing capacity of aluminum alloy thin-wall welded structures. According to experimental results, the relationship between hardness and ultimate tensile strength was investigated. And then, a tetra-material model of mismatched welded joints was established based on the hardness distribution, and the strength of mismatched welded joints was systematically investigated by numerical simulation. Additionally, the statistical analysis of the relationship between mismatched parameters and the strength of welded joints was conducted through the design of experiments (DOE). The results show that the existence of SZ exerts a crucial role in the loading capacity of the welded joint. The main effects and interactions of geometrical and mechanical properties parameters have a great influence on the load-bearing capacity of welded joints. Moreover, the proposed meta-models could effectively predict the strength of thin-wall welded structures, providing a guideline for evaluating the load-bearing capacity of the complex components with the welded structures. Highlights: The influence of mismatched parameters on the strength of welded joints are studied based on numerical simulation. Main effects, interactive effects and contributions of each mismatched parameter are analyzed by mathematical statistics. Regression model estimates the strength of the aluminum alloy butt welded joints with mismatched mechanical properties.